Changes in Physiological Condition of Broiler Chickens Sprayed with Water before Transportation - U Sara; D P Rahardja; H Sonjaya; M Azhar (Jurnal Ilmu Ternak dan Veteriner, 2022)
Transportation to the slaughterhouse is a series of processes that can cause high levels of stress in broilers. Heat stress will increase if the distance between the farm and the slaughterhouse is far. One of the solutions to overcome heat stress due to transportation is to do watering a few minutes before the transportation so that the broilers are still able to maintain their homeostatic conditions. This study aims to determine the effect of watering methods before transportation with different distances on the haematological, hormonal, and quality status of broiler chickens. This study was arranged based on a factorial randomized block design (RAK). A total of 54 broilers of the Cobb strain aged 35 days were divided into 2 treatments, namely; without watering (P0) and watering (P1). Chickens in each treatment were transported to the poultry slaughterhouse with 2 different distances; 30km (J1) and 60km (J2), as well as 1 control treatment (without transport) (J0). Watering is done just before the transportation process. The results showed that the transportation distance increased the yellowness value (b*) of the breast meat, decreased the brightness value (L*), and increased the pH of the broiler thigh meat (P0.05). Hematocrit values, hemoglobin levels, and concentrations of the hormone triiodothyronine (T3), other meat color components, as well as the pH of the breast meat, did not change significantly, both in terms of watering, distance traveled, and the interaction between the two (P0.05). The solution of water spraying before transportation on different distances could not restore the hematology and hormonal status, as well as the meat quality of the broiler.  However, the decline in meat quality was shown in transported broilers.